2008
DOI: 10.1016/j.yexcr.2007.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Cell specific differences between human adipose-derived and mesenchymal–stromal cells despite similar differentiation potentials

Abstract: Stromal cells from bone marrow and adipose tissue are attractive sources of adult progenitors for cell-based therapy. However, whether those cell populations represent intrinsically different cell types is still largely under debate. The aim of this study was to systematically and quantitatively compare adipose-derived stromal cells (ADSC) and bone marrow-derived multipotent mesenchymal-stromal cells (BM-MSC). The quantitative comparison was realized using Taqman Low Density Array, 2D electrophoresis and diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
189
5
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 309 publications
(215 citation statements)
references
References 43 publications
15
189
5
6
Order By: Relevance
“…AT is composed of adipocytes and various cell types among which are a population of multipotent progenitors, termed adipose stromal cells (ASCs) [4]. ASCs display similar but not identical features with their bone marrow (BM) counterparts, mesenchymal stromal cells (MSCs) [5][6][7][8][9]. Like MSCs, ASCs are endowed with multilineage mesodermal differentiation potentials and exhibit extensive paracrine and immune-modulatory properties [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…AT is composed of adipocytes and various cell types among which are a population of multipotent progenitors, termed adipose stromal cells (ASCs) [4]. ASCs display similar but not identical features with their bone marrow (BM) counterparts, mesenchymal stromal cells (MSCs) [5][6][7][8][9]. Like MSCs, ASCs are endowed with multilineage mesodermal differentiation potentials and exhibit extensive paracrine and immune-modulatory properties [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental studies have shown that adipose tissue-derived stem cells (ADSCs), a source of mesenchymal stem cells (MSCs), are self-renewing and capable of regenerating infracted myocardium by inducing myogenesis and angiogenesis (Hwangbo et al 2010;Lin et al 2010;Yu et al 2010). ADSCs and MSCs exhibit a highly similar gene expression profile (Noel et al 2008), and the stem cells isolated from adipose tissues share the same morphology, phenotype and in vitro differentiation ability with bone marrow. Moreover, cultured populations of ADSCs can be expanded rapidly, and long-term cultured cells retain their mesenchymal pluripotency (Ranera et al 2011).…”
mentioning
confidence: 99%
“…Investigations into the gene expression profiles of BM-MSCs and ASCs found that 13.2% of 384 genes examined were differentially expressed between the two populations. Although no identifying markers were specific to each population, genes more highly expressed by ASCs were mainly involved in cellular communication (FGF9, IL1R2, CCL3 and KDR) while those with higher expression by BM-MSCs were involved in WNT signaling and differentiation pathways (WNT11, WNT7B and SOX6 ) [25].…”
Section: Regen Med (Epub Ahead Of Print)mentioning
confidence: 98%